The effectiveness of environmental interpretation in ecotourism destination: The case of Kinabalu Park / Wan Nur Syazana Wan Mohamad Ariffin - Wan Nur Syazana, Wan Mohamad Ariffin (2018)
Ecotourism primarily takes place in protected areas. Although protected, ecotourism still poses a threat to the sensitive environment if not practiced carefully. Hence, visitors’ education is important in protected areas in order to mitigate the negative impacts on the environment. Interpretation plays an important role in visitors’ education and it aims to increase their level of awareness and understanding that could potentially lead to positive behavior change. This study puts a primary emphasis on quantitative method while the qualitative method is used to support the quantitative outcome. This study takes into account the impacts of interpretation on visitors’ knowledge, attitude, and behavioral intention in Kinabalu Park, Sabah, Malaysia. 200 sets pre-visit surveys were collected to analyze the visitors’ level of knowledge, attitude, and behavioral intention before they were exposed to interpretation. Another 190 sets of post-visit surveys were also collected to analyze the same indicators among visitors that had been exposed to interpretation in the park. Furthermore, both the samples in the pre- and post-visit surveys are independent of one another. The results indicate that visitors in Kinabalu Park had higher level of knowledge and more positive attitude after they were exposed to interpretation as observed in the post-visit samples but only to a certain extent. Despite the higher level of knowledge and attitude among the post-visit samples, the visitors’ intention to adopt environmentally responsible behaviors did not differ significantly between the pre- and the post-visit samples. Further observation found that interpretation in Kinabalu Park did not fully adopt the qualities of interpretation as highlighted in the EROT (enjoyable, relevant, organized, and thematic) framework resulting in the lack of difference between the pre- and post-visit samples in terms of their knowledge, attitude, and behavioral intention. Interpretation in Kinabalu Park is thematic and organized but it lacks enjoyable, relevant, and provoking materials to sustain the visitors’ attention. Thus there is a potential for interpretation in Kinabalu Park to be further improved based on the theme adopted in its interpretation. Both knowledge and attitude are important determinants in predicting a person’s intention to engage in environmentally responsible behaviors. Therefore, interpretation in Kinabalu Park has to first focus in making the visitors more knowledgeable and shifting their attitude towards the environment.